2017
DOI: 10.1007/s00894-016-3192-9
|View full text |Cite
|
Sign up to set email alerts
|

Docking and molecular dynamics studies on triclosan derivatives binding to FabI

Abstract: FabI, enoyl-ACP reductase (ENR), is the rate-limiting enzyme in the last step for fatty acids biosynthesis in many bacteria. Triclosan (TCL) is a commercial bactericide, and as a FabI inhibitor, it can depress the substrate (trans-2-enoyl-ACP) binding with FabI to hinder the fatty acid synthesis. The structure-activity relationship between TCL derivatives and FabI protein has already been acknowledged, however, their combination at the molecular level has never been investigated. This paper uses the computer-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Meanwhile, the monomer simulations showed disordered movements of the SBL and active site (Figure ). This conformation diversity was previously observed, to a lesser extent, in shorter simulations (50 ns), where the SBL assumed different folding profiles (α-helix or 3-10 helix) . The relevance of these states is also corroborated by structural information from other organisms’ crystal structures, such as Burkholderia pseudomallei and A.…”
Section: Discussionsupporting
confidence: 75%
“…Meanwhile, the monomer simulations showed disordered movements of the SBL and active site (Figure ). This conformation diversity was previously observed, to a lesser extent, in shorter simulations (50 ns), where the SBL assumed different folding profiles (α-helix or 3-10 helix) . The relevance of these states is also corroborated by structural information from other organisms’ crystal structures, such as Burkholderia pseudomallei and A.…”
Section: Discussionsupporting
confidence: 75%
“…The MM-PB(GB)SA approach has been applied in a number of studies, including the development of anticancer compounds [222][223][224], antibacterial [225][226][227], antiviral [228][229][230][231][232] and antiparasitic drugs [233][234][235], as well as antipsychotics [236,237]. These methods are also often applied to understand and analyze the binding mode and key interactions of small molecules [238,239] as well as peptide [240,241] and protein ligands [242] at their targets.…”
Section: Binding Energy Estimationmentioning
confidence: 99%
“…Yang and collaborators (2017) have already analysed the structural potential of triclosan derivatives by interpreting 50 ns long MD simulations with several TCL derivatives . They have shown that the loop covering the active site can assume structured conformation upon ligand binding.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in the same work, it was reported the absence of π‐π interaction between the inactive compound 23 and the twin tyrosine residues, which partially agrees with our observations regarding the stabilisation importance (Figure B). According to Yang, mostly hydrophobic residues favourably contributed to the binding energy, namely Leu100, Met159, Ala196, Ala197, Ile200, Phe203. This amino‐acid set agrees with our CSM's suggestion that hydrophobic chemical features are relevant to discern differences in the biological activity.…”
Section: Resultsmentioning
confidence: 99%